On Inverse and Implicit Function Theorem for Sobolev Mappings - Cristea, Mihai (Axioms, 2025)
We extend Clarke’s local inversion theorem for Sobolev mappings. We use this result to find a general implicit function theorem for continuous locally Lipschitz mapping in the first variable and satisfying just a topological condition in the second variable. An application to control systems is given.